Défis associés à l’offre de services de santé et de services sociaux en français au Manitoba : perceptions des professionnels - de Moissac, Danielle; de Rocquigny, Janelle; Giasson, Florette; Tremblay, Cindy-Lynne; Aubin, Natalie; Charron, Marc; Allaire, Gratien (Reflets, 2012)
Les services de santé et les services sociaux en français ne sont accessibles qu’auprès d’un quart de la population francophone au Manitoba (de Moissac, 2011). Une pénurie de professionnels pouvant offrir des services en français est perçue comme un obstacle important pour les usagers qui recherchent ces services et pour les professionnels qui voudraient assurer un suivi en français pour leurs clients. Une hésitation à s’identifier comme francophone et un manque de connaissance des ressources disponibles en français contribuent-ils à cette perception de pénurie? Cet article traite des défis entourant l’offre de services de santé et de services sociaux en français au Manitoba et suggère des pistes de solutions. Mots-clés : disponibilité, accessibilité, minorité francophone, Manitoba, professionnels

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Reference framework: Training for active offer of French-language health services - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)